2010
DOI: 10.1115/1.4000229
|View full text |Cite
|
Sign up to set email alerts
|

On the Effective Elastic Properties of Macroscopically Isotropic Media Containing Randomly Dispersed Spherical Particles

Abstract: A computational scheme for estimating the effective elastic properties of a particle rein forced matrix is investigated. The randomly distributed same-sized spherical particles are assumed to result in a composite material that is macroscopically isotropic. The scheme results in a computational efficient method to establish the correct bulk and shear moduli by representing the three-dimensional (3D) structure in a two-dimensional configuration. To this end, the statistically equivalent area fraction is defined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Large deviations between the MT predictions and the FEM results occur primarily for the effective Poisson's ratio, which is generally underestimated by the MT for higher porosity levels. These findings are of practical relevance for the homogenisation of porous thin films and perforated layers, as well as for the evaluation of the in-plane properties of cellular solids under plane stress conditions, and might, with limitations, even be used to estimate the effective properties of RVEs with random distributions of spherical pores, as discussed by Cojocaru and Karlsson (2010) and Fiedler et al (2010). The effective elastic properties of such materials can be conveniently predicted using both the SCM and the MT if their level of porosity lies within the stated intervals.…”
Section: Discussionmentioning
confidence: 90%
“…Large deviations between the MT predictions and the FEM results occur primarily for the effective Poisson's ratio, which is generally underestimated by the MT for higher porosity levels. These findings are of practical relevance for the homogenisation of porous thin films and perforated layers, as well as for the evaluation of the in-plane properties of cellular solids under plane stress conditions, and might, with limitations, even be used to estimate the effective properties of RVEs with random distributions of spherical pores, as discussed by Cojocaru and Karlsson (2010) and Fiedler et al (2010). The effective elastic properties of such materials can be conveniently predicted using both the SCM and the MT if their level of porosity lies within the stated intervals.…”
Section: Discussionmentioning
confidence: 90%
“…The Finite Element Method (FEM) has been the most commonly used technique for computing the local fields in heterogeneous materials (Llorca et al, 2000;Bohm et al, 2002;Segurado and Llorca, 2002;Kari et al, 2007;Barello and Lévesque, 2008;Klusemann and Svendsen, 2010;Cojocaru and Karlsson, 2010;ElMourid et al, 2012;Pahlavanpour et al, 2013;Moussaddy et al, 2013). The method consists of meshing a unit cell and computing the local fields when it is submitted to an external load.…”
Section: Computation Of Local Fields In Heterogeneous Materialsmentioning
confidence: 99%
“…Kari et al (2007) used RVEs for computing the properties of fiber-reinforced composites. Cojocaru and Karlsson (2010) reduced the RVE to an equivalent representative area to predict the effective elastic properties of a material composed of spherical particles dispersed in a matrix. The concept of RVE was given a statistical definition by Kanit et al (2003), who conducted a statistical study and showed that the effective properties can be computed within a prescribed accuracy by increasing the number of statistical realizations, provided that the bias in mechanical properties is overcome.…”
Section: Numerical Homogenizationmentioning
confidence: 99%